![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. \(\left(2x-3\right)\left(x+1\right)+\left(2x-3\right)\left(3x-7\right)=0\)
\(\Leftrightarrow\left(2x-3\right)\left(x+1+3x-7\right)=0\)
\(\Leftrightarrow\left(2x-3\right)\left(4x-6\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}2x-3=0\\4x-6=0\end{matrix}\right.\)\(\Leftrightarrow x=\dfrac{3}{2}\)
b. \(\left(x-4\right)\left(3x-2\right)+x^2-16=0\)
\(\Leftrightarrow\left(x-4\right)\left(3x-2\right)+\left(x-4\right)\left(x+4\right)=0\)
\(\Leftrightarrow\left(x-4\right)\left(3x-2+x+4\right)=0\)
\(\Leftrightarrow\left(x-4\right)\left(4x+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-4=0\\4x+2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=4\\x=-\dfrac{1}{2}\end{matrix}\right.\)
(2x-3)(x+1)+(2x+3)(3x-7)=0
<=> (2x-3)(x+1)-(2x-3)(3x-7)=0
<=> (2x-3)(x+1-3x+7)=0
<=> (2x-3)(-2x+8)=0
<=> 2x-3=0 => x=3/2
Hoặc -2x+8=0 => x= 4
Vậy x thuộc{3/2;4}
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(A=x^2+2\cdot\frac{1}{2}x+\frac{1}{4}-\frac{9}{4}=\left(x+\frac{1}{2}\right)^2-\frac{9}{4}\)
=> \(A\ge-\frac{9}{4}\) dấu = xảy ra khi : \(x=\frac{-1}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(5x-2)(3x+1)+(7-15x)(x+3)=-20
<=> 15x2+5x-6x-2+7x+21-15x2-45x+20=0
<=>39-39x=0
<=>39(1-x)=0
<=>1-x=0
=>x=1
(5x-2)(3x+1)+(7-15x)(x+3)=-20
=>\(15x^2-6x+5x-2+7x-15^2+21-45x=-20\)
=>\(-39x+19=-20\)
=>\(-39x=-39\)
=>\(x=1\)
vậy x=1
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 2:
\(A=-2x^2+3x-5\)
\(=-2\left(x^2+\frac{3x}{2}-\frac{5}{2}\right)\)
\(=-2\left(x^2-\frac{3x}{2}+\frac{9}{16}\right)-\frac{31}{8}\)
\(=-2\left(x-\frac{3}{4}\right)^2-\frac{31}{8}\le-\frac{31}{8}\)
Dấu = khi \(-2\left(x-\frac{3}{4}\right)^2=0\Leftrightarrow x-\frac{3}{4}=0\Leftrightarrow x=\frac{3}{4}\)
Vậy \(Max_A=-\frac{31}{8}\Leftrightarrow x=\frac{3}{4}\)
\(\left(x-1\right)\left(3x-7\right)=\left(x-1\right)\left(x+3\right)\)
\(\Leftrightarrow\left(x+1\right)\left(3x-7\right)-\left(x+1\right)\left(x+3\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(\left(3x-7\right)-\left(x+3\right)\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(3x-7-x-3\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(2x-10\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x+1=0\\2x-10=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-1\\x=5\end{cases}}\)
(x-1)(3X-7)=(x-1)(x+3)
=>(x-1)(3x-7)-(x-1)(x+3)=0
=>(x-1)(3x-7-x-3)=0
=>(x-1)(2x-10)=0
=> + x-1=0 =>x=1
+ 2x-10=0 =>x=5